Risk factors for bronchiolitis obliterans complicating adenovirus pneumonia in children: a meta-analysis - Yao, Mei-mei; Gao, Tian-ji; Zhao, Min; Fu, Yan-hua; Liu, Jing; Wang, Tian-jiao; Yang, Ying (Frontiers in Pediatrics, 2024)
Objective: To preliminarily explore the risk factors for post‐infectious bronchiolitis obliterans (PIBO) complicating adenovirus pneumonia (ADVP) in children through a meta‐analysis. Methods: A systematic search was conducted on three English-language databases (PubMed, Web of Science and The National Library of Medicine) and two Chinese-language databases (China National Knowledge Infrastructure and the Wanfang Database) between database inception and 1 January 2023. Data analysis was conducted using Stata 15.1 software. Results: A total of 10 articles, reporting 14 risk factors, were included in the analysis, with 8 risk factors taken into consideration. Through the meta‐analysis, 5 risk factors were identified for PIBO complicating ADVP in paediatric patients: hypoxaemia (odds ratio [OR] = 9.37, 95% CI: 4.22, 20.77, p < 0.001), persistent wheezing (OR = 4.65, 95% CI: 2.20, 9.82, p < 0.001), mechanical ventilation (OR = 3.87, 95% CI: 2.37, 6.33, p < 0.001), length of hospital stay (LoHS) (OR = 1.25, 95% CI: 1.09, 1.43, p < 0.001) and fever duration (OR = 1.08, 95% CI: 1.02, 1.14, p = 0.009). Conclusion: Existing evidence suggests that hypoxaemia, persistent wheezing, mechanical ventilation, LoHS and fever duration are risk factors for PIBO complicating ADVP in children. These findings underscore the need for enhanced assessment and management in clinical practice. This study may provide such a clinical prediction model from the identified 5 risk factors for PIBO and offer valuable insights for preventing bronchiolitis obliterans in children with ADVP.